The contribution of the immune system to parturition - R. De Jongh; Ph. Jorens; I. Student; R. Heylen (Mediators of Inflammation)
The immune system plays a central role before and during parturition, including the main physiological processes of parturition: uterine contractions and cervical ripening. The immune system comprises white blood cells and their secretions. Polymorphonuclear cells and macrophages invade the cervical tissue and release compounds, such as oxygen radicals and enzymes, which break down the cervical matrix to allow softening and dilatation. During this inflammatory process, white blood cells undergo chemotaxis, adherence to endothelial cells, diapedesis, migration and activation. Factors that regulate white blood cell invasion and secretion include cytokines such as tumour necrosis factor and interleukins. Glucocorticoids, sex hormones and prostaglandins, affect cytokine synthesis. They also modulate the target cells, resulting in altered responses to cytokines. On the other hand, the immune system has profound effects on the hormonal system and prostaglandin synthesis. In animals, nitric oxide has marked effects on uterine quiescence during gestation. At the same time, it plays an important role in regulating the vascular tone of uterine arteries and has anti-adhesive effects on leukocytes. Cytokines are found in amniotic fluid, and in maternal and foetal serum at term and preterm. Several intrauterine cells have been shown to produce these cytoldnes. Since neither white blood cells, cytokines nor nitric oxide seem to be the ultimate intermediate for human parturition, the immune system is an additional but obligatory and underestimated component in the physiology of delivery. Scientists, obstetricians and anaesthesiologists must thus be aware of these processes.